Analisis Pengaruh Manajemen Karir, Motivasi, Dan Lingkungan Kerja Terhadap Karir Karyawan U.D. Karya Pala Kediri - Saras, Yogi S; Mega Hastuti, Sri Wahyuni; Maheri Laksono, Sonny Subroto (Universitas Islam Kadiri, 2024)
This study analyzes the impact of Career Management, Motivation, and Work Environment on Employee Careers at UD Karya Pala Kediri. It aims to evaluate both the simultaneous and partial effects of these factors on employee careers at the company. Using a quantitative explanatory research method, data were collected through questionnaires and interviews for primary data, and company documentation along with related sources for secondary data. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS). The results show that career management, motivation, and work environment all significantly affect employee careers simultaneously, with motivation having the strongest impact. These findings highlight that enhancing employee motivation will have the greatest effect on improving their careers